Experimental studies on the axial compression behavior of hollow sandwich concrete GFRP-steel tube composite short columns. (16th May 2023) - Wang, Tongkuai; Yang, Wenwei; Yin, Chaozheng
Highlights: Axial compression performance of GFRP-steel tube confined concrete columns. GFRP tube thickness and hollow ratio are important parameters affecting the specimen. DSTCs with reasonable hollow ratio can meet the same mechanical properties as DTCC. A calculation model was derived for the axial compression bearing capacity of DSTCs. Abstract: This paper explores the mechanical mechanisms and properties of hollow-sandwich concrete GFRP–steel tube composite short columns under axial compression to promote their application in the practical engineering of bridge piers under high-salinity and high-humidity corrosion environments. The force action, stress state and mechanical calculation model of composite short columns are important manifestations reflecting the mechanical mechanism, and the mechanical properties are measured by failure characteristics, bearing capacity, initial stiffness, ductility coefficient, energy dissipation value, damage coefficient and load–displacement curve. In this paper, an axial compression test of 15 composite short columns was designed and carried out with the parameters of section form, GFRP tube thickness, concrete strength, hollow ratio and steel tube thickness. The results showed that the specimens exhibited typical local pressure or shear failure, which is characterized by tearing of the GFRP tube fiber. The built-in steel tube can improve the ultimate bearing capacity of the specimen, and the ductility and axial compression energy dissipation of the double-tube concrete short column (DTCC) is basically consistent with hollow sandwich concrete GFRP-steel tube composite short columns (DSTCs). With a reasonable hollow ratio, the DSTCs can meet the same mechanical properties and deformation performance requirements as the DTCC. Compared with concrete strength and steel tube thickness, the influence of GFRP tube thickness and hollow ratio on the ultimate bearing capacity of specimens is more obvious. Under the action of axial compression, the sandwich concrete is changed from a unidirectional compression state to a complex three-dimensional compression-confined concrete. The GFRP tube and steel tube change from unidirectional compression to a bidirectional stress state. Based on the plastic theory analysis, considering the influence of uneven distribution of the concrete stress state along the radial direction, the calculation model of axial compression bearing capacity of hollow sandwich concrete GFRP-steel tube composite short columns is derived. The calculation results are in good agreement with the experimental results.